Mission San Gabriel. - Unknown:::Creator::::::::::::
View of Mission San Gabriel with it's campanario (bell wall) and pillar-like buttresses with pyramidal finials. A row of low growing palms grow alongside the mission. The photograph is a sepia image with a yellow border.